A FIB-SEM Study on Correlations between PEFC Electrocatalyst Microstructure and Cell Performance. (14th September 2015) - Okumura, Makito; Nagamatsu, Yohei; Noda, Zhiyun; Tachikawa, Yuya; Daio, Takeshi; Hayashi, Akari; Sasaki, Kazunari
Abstract : PEFC electrocatalyst microstructure strongly influences cell performance. In this study, Nafion ionomer content in the cathode electrocatalyst layer is systematically varied to modify the electrocatalyst microstructure. Current-voltage characteristics of the membrane-electrode-assemblies are measured and then the electrocatalyst microstructure is observed by the focused-ion-beam coupled scanning electron microscopy (FIB-SEM) to examine the correlations between the 3D microstructure and the cell performance. Although technical limitation was found for FIB-SEM analysis, certain correlations were also established.